Determination Of Optimum Drying Condition On Flavonoid Content Of Ficus Carica L. Leaves Using Tray Dryer - Emma Hermawati; Yusmardhany Yusuf; Alfiana Adhitasari (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
This research aims to find out the characteristics of Ficus carica L. drying process using a tray dryer and determine the effect of temperature and drying time on Ficus Carica L. flavonoid content using a tray dryer to obtain Ficus carica L. herbal leaf tea which is high in antioxidants. At the experimental stage, the water content of fresh leaves of Ficus carica L. were determined, so the water content is 74 ± 1.11% (wet base), then dried using a tray dryer at 35; 40; 45; 50; and 55oC, with a variation of the drying air flow rate of 1.3; 1.6; 1.9; 2.2; and 2.4 m/s. The optimum temperature and drying air flow rate are 50oC and 1.9 m/s since the highest flavonoid content was obtained at those condition as much 0.78 ± 0.001 gram QE/100gram extract. Dried products which packaged in tea bags have a content of 23.60% carbohydrate, total fat 3.50%, protein 5.35%,antioxidant 154.25 ppm and calorific value of 1430 Kcal/100 grams. It can be concluded that Ficus carica L. drying process using a tray dryer can be used to produce herbal leaf tea which is high in antioxidants and flavonoid content.